Factors Influencing the Entrepreneurial Practices of Subsidiaries: Observations from Bulgaria - Naumov, Marko (2012)
Various authors have examined the entrepreneurial practices within multinationals. However, it is not yet known what is the relationship between entrepreneurial (or innovative) parent firms and their subsidiaries, and why some subsidiaries are allowed to implement entrepreneurial activities while others are not. The current dissertation tries to find the answer of these questions by interweaving the institutional theory and the entrepreneurial orientation theory. The former is applied in order to explain the influence of the external environment on the subsidiaries’ actions, whereas the latter helps to elucidate the nature of entrepreneurial practices. This dissertation also presents an exploratory research design, and the study consists of five semi-structured interviews with managers from Bulgaria. The findings suggest that there are three main factors that restrict domestic subsidiaries to undertake entrepreneurial activities which are market size, host country’s business environment, and corporate policy. The observations indicate, too, that although corporate policy appears to be the most decisive factor, it can be influenced by the other two. In simple terms, subsidiaries which are located in large markets with favourable business environment would be permitted to perform entrepreneurial activities.